Architecture of WEB-oriented system of virtual laboratories in grid-infrastructure - Salnikov, A.O.; Sliusar Є.А.; Anisimov, M.I.; Levchenko, P.I.; Maryanovskiy, B.A.; Desiatnik Н.П.; Cheredarchuk, A.I.; Sudakov, O.O. (Journal of Information Technologies in Education (ITE), 2009)
Analysis of existing systems for control of Grid jobs is given. Testing of three systems (LAP, P_GRADE, BIOSYMGRID) were performed on the grid-resource of National Taras Shevchenko University of Kyiv. Comparison of tested systems is given. Requirements to the atrchictecture of complex web-oriented system of virtual laboratories in Grid-infrastructure for scientific and educational institutions of Ukraine were developped.